PATIENT SATISFACTION EVALUATION ON HOSPITALS; COMPARISON STUDY BETWEEN ACCREDITED AND NON ACCREDITED HOSPITALS IN JORDAN - Ajarmah, Balqees Salem; Hashem, Tareq N. (European Scientific Journal, ESJ, 2015)
The research aim is to compare accredited and non-accredited hospitals in relation to patient's satisfaction in Jordan and to address the question if there is a correlation between patient's satisfaction and accreditation. The researchers adopt a quantitative methodology. T test was used to test the main hypotheses. Patient satisfaction was measured using the SERVQUAL scale (tangibility, reliability, responsiveness, assurance and empathy). 1000 questionnaires were distributed to stratified random sample of hospitals' inpatients. The results show considerable evidence that accreditation significantly improves patients' satisfaction. Accordingly, accreditation programs should be reinforced as a tool to improve health service quality.